Exploring the risks and benefits of flexibility in biodiversity offset location in a case study of migratory shorebirds. Issue 2 (15th December 2022) - Shumway, Nicole; Saunders, Megan I.; Nicol, Sam; Fuller, Richard A.; Ben‐Moshe, Noam; Iwamura, Takuya; Kim, Sun W.; Murray, Nicholas J.; Watson, James E. M.; Maron, Martine
Abstract: Biodiversity offsets aim to counterbalance the residual impacts of development on species and ecosystems. Guidance documents explicitly recommend that biodiversity offset actions be located close to the location of impact because of higher potential for similar ecological conditions, but allowing greater spatial flexibility has been proposed. We examined the circumstances under which offsets distant from the impact location could be more likely to achieve no net loss or provide better ecological outcomes than offsets close to the impact area. We applied a graphical model for migratory shorebirds in the East Asian–Australasian Flyway as a case study to explore the problems that arise when incorporating spatial flexibility into offset planning. Spatially flexible offsets may alleviate impacts more effectively than local offsets; however, the risks involved can be substantial. For our case study, there were inadequate data to make robust conclusions about the effectiveness and equivalence of distant habitat‐based offsets for migratory shorebirds. Decisions around offset placement should be driven by the potential to achieve equivalent ecological outcomes; however, when considering more distant offsets, there is a need to evaluate the likely increased risks alongside the potential benefits. Although spatially flexible offsets have the potential to provide more cost‐effective biodiversity outcomes and more cobenefits, our case study showed the difficulty of demonstrating these benefits in practice and the potential risks that need to be considered to ensure effective offset placement. Abstract : Estudio de los riesgos y beneficios de la flexibilidad en la ubicación de compensación de la biodiversidad en el estudio de caso de aves costeras migratorias Resumen: Las compensaciones de la biodiversidad buscan contrabalancear el impacto residual que tiene el desarrollo sobre las especies y los ecosistemas. Los documentos guía recomiendan explícitamente que las acciones de estas compensaciones estén ubicadas cerca del lugar del impacto debido al potencial elevado de que haya condiciones ecológicas similares, aunque ya hay propuestas de una mayor flexibilidad espacial. Analizamos las circunstancias bajo las cuales las compensaciones alejadas del lugar de impacto tendrían mayor probabilidad de lograr pérdidas netas nulas o de proporcionar mejores resultados ecológicos que las compensaciones cercanas al área de impacto. Aplicamos un modelo gráfico para las aves costeras migratorias en el corredor aéreo asiático‐australasiático del este como estudio de caso para estudiar los problemas que surgen cuando se incorpora la flexibilidad espacial a la planeación de las compensaciones. Las compensaciones espacialmente flexibles pueden mitigar los impactos más efectivamente que las compensaciones locales; sin embargo, los riesgos que esto involucra pueden ser considerables. En nuestro estudio de caso hubo datos insuficientes para concluir contundentemente sobre la efectividad y equivalencia de las compensaciones basadas en los hábitats distantes para las aves costeras migratorias. Las decisiones en torno a la ubicación de las compensaciones deberían estar impulsadas por el potencial para obtener resultados ecológicos equivalentes; sin embargo, al considerar compensaciones más alejadas, existe la necesidad de evaluar el incremento probable de riesgos junto a los beneficios potenciales. Aunque las compensaciones espacialmente flexibles tienen el potencial para proporcionar resultados más rentables y más beneficios colaterales, nuestro estudio de caso mostró la dificultad para demostrar estos beneficios en la práctica y los riesgos potenciales que necesitan considerarse para asegurar una ubicación efectiva de las compensaciones. 【摘要】: 生物多样性补偿旨在抵消发展对物种和生态系统的残留影响。生物多样性补偿的指导文件明确建议, 补偿行动应在受影响地点的附近进行, 因为相似的生态条件具有较大的补偿潜力, 但也有人提出补偿地点的选择应允许更高的空间灵活性。我们研究了在什么情况下, 远离影响地点的补偿行动比靠近影响地点的补偿行动更有可能实现无净丧失或产生更好的生态结果。本研究以迁徙滨鸟在东亚‐澳大利亚的飞行路径为例, 应用图形模型探究了将空间灵活性纳入生物多样性补偿规划时出现的问题。空间上灵活的补偿有可能比原地点附近的补偿更有效地减缓影响;然而, 也可能涉及巨大的风险。在我们的案例研究中, 没有足够的数据来对远距离的基于栖息地的迁徙滨鸟生物多样性补偿的有效性和等价性做出有力结论。补偿地点的选择应该由实现等价生态结果的潜力所驱动;然而, 当考虑更远距离的补偿时, 还需要评估可能增加的风险和潜在的好处。虽然空间上灵活的补偿有可能提供更具成本效益的生物多样性结果和更多的共同利益, 但我们的案例研究表明, 在实践中证明这些利益尚面临困难, 研究同时指出了为确保补偿地点的有效性需要考虑的潜在风险。【翻译:胡怡思;审校:聂永刚】